Multicointegration in US consumption data - Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The present paper tests for the existence of multicointegration between real per capita private consumption expenditure and real per capita disposable personal income in the USA. In doing so, we exploit the fact that the flows of disposable income and consumption expenditure on the one hand, and the stock of consumers? wealth, which can be considered as cumulative past discrepancies between the flows of income and expenditure, on the other hand, can be thought of as a stock-flow model, in which multicointegration is likely to occur. We apply recently developed I(2) techniques for testing for multicointegrating relations and find supporting evidence for the existence of multicointegration in US consumption data.
Keywords: C12; C13; C22; C32; C51; E21; 330; Cointegration; multicointegration; I(2) processes; consumption; Verbraucherausgaben; Verfügbares Einkommen; Kointegration; Vereinigte Staaten